Dissemination of climate-smart and sustainable agriculture innovations through AICCRA partnerships for resilient livelihoods among small-scale farmers in Kenya's ASAL regions - Nduah Alex; Ogutu, Elizabeth; Gichunge, Karen; Nzuki, Esther (2025)
This report provides a comprehensive summary of the climate-smart agriculture (CSA), sustainable, and good agricultural practices(GAP) implemented under the AICCRA Kenya project through seven key partners: the African Conservation Tillage Network (ACTN), Murang’a University of Technology (MUT), Laikipia University (LU), Taita Taveta University (TTU), Chuka University (CU), Kimatwa Women’s SACCO, and Lewa Wildlife Conservancy (LWC). Operating across diverse agro-ecological zones, these partners promote technologies that enhance productivity, resilience, and environmental sustainability among smallholder farmers in Kenya. The core CSA practices include soil and water conservation methods such as drip irrigation, Zai pits, tied ridges, and basin tillage; conservation agriculture techniques emphasizing minimum soil disturbance, residue retention, and crop diversification; agroforestry; drought-tolerant varieties; and integrated crop– livestock systems. The report highlights the outcomes of capacity-building initiatives that have trained more than 12,000 farmers, improving soil health, water use efficiency, and livelihood resilience. In combining education, training, innovation, and landscape-level conservation, AICCRA–Kenya showcases a transformative model for scaling climate-resilient and sustainable agriculture in Kenya’s arid and semi-arid lands (ASALs).